2009
DOI: 10.1017/s0007114509288994
|View full text |Cite
|
Sign up to set email alerts
|

Periconception folic acid supplementation, fetal growth and the risks of low birth weight and preterm birth: the Generation R Study

Abstract: Countries worldwide, including the Netherlands, recommend that women planning pregnancy use a folic acid supplement during the periconception period. Some countries even fortify staple foods with folic acid. These recommendations mainly focus on the prevention of neural tube defects, despite increasing evidence that folic acid may also influence birth weight. We examined whether periconception folic acid supplementation affects fetal growth and the risks of low birth weight, small for gestational age (SGA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(173 citation statements)
references
References 52 publications
(84 reference statements)
8
161
0
4
Order By: Relevance
“…Hypermethylation of the H19 DMR has been linked to relaxation of imprint controls, increased transcription and translation of the potent IGF2 growth mitogen, 58 and higher birth weight. 59 Our findings are consistent with those of previous studies in which FA intake before or/and during pregnancy or folate levels were associated with DNA methylation differences of a similar magnitude at this imprinted domain [46][47][48][49]60 and early childhood obesity. [61][62][63] Similar to the IGF2/H19 imprinted domain where IGF2 and H19 are reciprocally imprinted, the DLK1 and MEG3 genes, located on chromosome 14q32.2, are also reciprocally imprinted.…”
Section: Discussionsupporting
confidence: 91%
“…Hypermethylation of the H19 DMR has been linked to relaxation of imprint controls, increased transcription and translation of the potent IGF2 growth mitogen, 58 and higher birth weight. 59 Our findings are consistent with those of previous studies in which FA intake before or/and during pregnancy or folate levels were associated with DNA methylation differences of a similar magnitude at this imprinted domain [46][47][48][49]60 and early childhood obesity. [61][62][63] Similar to the IGF2/H19 imprinted domain where IGF2 and H19 are reciprocally imprinted, the DLK1 and MEG3 genes, located on chromosome 14q32.2, are also reciprocally imprinted.…”
Section: Discussionsupporting
confidence: 91%
“…Various sociodemographic and lifestyle related determinant seems to affect these fetal growth and birth outcomes [114][115][116][117][118][119]. Also, specific fetal growth patterns seem to be associated with outcomes in childhood [120][121][122][123]. We have demonstrated in a subgroup study among mothers with a known and reliable last menstrual period, that various life style related factors affect first trimester growth [124].…”
Section: Questionnairesmentioning
confidence: 79%
“…Micronutrient supplementation before pregnancy also warrants further research. 42,43 Among Bhutanese refugees dependent on food aid, the incidence of low birth weight declined from 16% to 8% after 2 to 3 years of implementation of micronutrientfortified blended foods. 44 In conclusion, we found that maternal micronutrient supplementation can reduce the risk of low birth weight but has no overall effect on perinatal mortality in developing countries.…”
Section: Discussionmentioning
confidence: 99%